HUMAN-COMPUTER INTERACTION (HCI) IN A WEB-BASED STUDENT LEARNING OUTCOME MONITORING SYSTEM USING USER CENTERED DESIGN (UCD) (Jurnal Pilar Nusa Mandiri, 2023)
Student learning outcomes in the learning process at school are usually expressed in the form of scores. This learning result is not only useful as feedback for students but also useful for parents and teachers. For parents, student learning outcomes are used as a reference to provide assistance in the form of attention, guidance, motivation, and others. As for teachers, learning outcomes are used as a benchmark to analyze the success of the teaching process that has been passed. Human Computer Interaction (HCI) is a scientific discipline that examines communication or interaction between users and systems. It was concluded that 73% of parents/guardians agreed to use the Student Learning Outcomes Monitoring System in the form of a student learning monitoring application to monitor children's learning progress at school.